ASSESSMENT OF THE HEALTH RISK OF THE POPULATION OF AN INDUSTRIAL CITY DUE TO THE IMPACT OF THE EMISSIONS FROM A METALLURGICAL ENTERPRISE - Кислицына, Вера Викторовна; Суржиков, Дмитрий Вячеславович; Голиков, Роман Анатольевич; Корсакова, Татьяна Георгиевна (Medicine in Kuzbass, 2022)
The aim of the research was to assess the risk of public health damage due to the impact of atmospheric emissions from the rolling-mill production of a metallurgical plant. Materials and methods. The volume of maximum allowable emissions of the enterprise was used in the work. Calculations of the maximum one-time and average annual concentrations of substances at the selected points associated with residential development microdistricts were carried out using the «ECOcenter-Standard» program. Public health risks were calculated on the basis of the Guideline R 2.1.10.1920-04 and the methods of Shcherbo A.P. and Onishchenko G.G. The resulting risk levels were compared with the acceptable values. Also in the work, risks were determined taking into account the background concentrations of pollutants. Results. Priority pollutants were identified: iron oxide (III), nitrogen dioxide, nitrogen oxide, sulfur dioxide, carbon monoxide, benzo(a)pyrene. The maximum one-time and average annual concentrations of substances at the selected points were determined, an excess of the maximum allowable concentration of iron oxide was revealed. The highest risk levels of chronic intoxication were identified from the exposure to iron oxide and nitrogen dioxide. The maximum total risk level of chronic intoxication was observed in the area of the Kuzbass Fair due to the influence of nitrogen dioxide, which was because of the close location of pollution sources. The total values of carcinogenic risk and the risk of immediate action were below the level of acceptable risk for all points. The total values of the risk of chronic intoxication significantly exceeded the acceptable level at individual points. The carcinogenic risk and the risk of chronic intoxication, taking into account the impact of background concentrations of substances, significantly exceeded the acceptable level. Conclusion. Atmospheric emissions from the rolling-mill production of the metallurgical plant contribute to the pollution of the city’s atmospheric air increasing the risk of chronic intoxication.